Rancang Bangun Penyiraman Tanaman Pintar Menggunakan Smartphone dan Mikrokontroler Arduino Berbasis Internet of Thing - Arif Setyo Pambudi; Septi Andryana; Aris Gunaryati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Everyday busy making plant owners leave their plants, this causes their plants to wither or die, in this study aims to build a smart watering system for plants using the Blynk smartphone application that has been integrated with the Arduino Uno R3 mikrocontroller because it is connected through software Arduino IDE program input to run as desired an which is equipped with a Relay 5V tool deliver voltage, and Aquarium Pumps so that water can flow to plants. Then for Thingspeak it self, it useful to display the moisture value in the soil that will be displayed on the web that has been connected with the Arduino Uno R3. Soil Moisture Sensor to let you know if the soil content is below 400 then the soil is most moist and if the soil above 900  the soil status dry, trough this Smartphone can water the plants with time or use the on / off button that is already available in the Blynk Smartphone app view